Faktor-Faktor yang Memengaruhi Pemilihan Metode Decommissioning Platform Lepas Pantai - Zahra Wardana; Tri Joko Wahyu Adi (LPPM Universitas Abdurrab, 2026)
Offshore platform decommissioning represents the final stage in the life cycle of oil and gas infrastructure, characterized by complexity, high risk, and substantial costs. The selection of decommissioning methods, such as complete removal, partial removal, and toppling, requires careful consideration of various technical, logistical, financial, risk-related, and environmental factors. This study aims to identify the factors influencing offshore platform decommissioning method selection and analyze the relationships among these factors using a dependency matrix approach based on assessments by five offshore experts. The findings identified nine significant factors influencing method selection. The results of this research provide a foundational framework for developing a more systematic, contextual, and practical decision-making approach for offshore platform decommissioning activities in Indonesia